Glioblastoma niches: from the concept to the phenotypical reality - Schiffer, Davide; Mellai, Marta; Bovio, Enrica; Bisogno, Ilaria; Casalone, Cristina; Annovazzi, Laura (Neurological sciences, 2018)
Recently, the concept of niches as sites of tumor progression, invasion, and angiogenesis in glioblastoma (GB) has been extensively debated. Niches, considered the sites in which glioblastoma stem cells (GSCs) reside, have been classified as perivascular, perinecrotic, and invasive. However, from a neuropathological point of view, it is not easy to establish when a tumor structure can be considered a niche. The relevant literature has been reviewed in the light of our recent experience on the subject. As for perinecrotic niches, the occurrence of GSCs around necrosis is interpreted as triggered by hypoxia through HIF-1α. Our alternative hypothesis is that, together with progenitors, they are the cell constituents of hyper-proliferative areas of GB, where perinecrotic niches have developed, and they would, therefore, represent the remnants of GSCs/progenitors spared by the developing necrosis. Perivascular structures originate from both transport vessels and exchange vessels, i.e., venules, arterioles, or the undefinable neo-formed small vessels, but only those in which a direct contact between GSCs/progenitors and endothelial cells occurs can be called niches. Both pericytes and microglia/macrophages play a role in niche function: Macrophages of blood origin invade GB only after the appearance of “mother vessels” with consequent blood-brain barrier disruption. Not all vessel/tumor cell structures can be considered niches, that is, crucial sites of tumor progression, invasion, and angiogenesis.